Association Between Early Hyperoxia Exposure After Resuscitation From Cardiac Arrest and Neurological Disability: Prospective Multicenter Protocol-Directed Cohort Study. Issue 20 (15th May 2018) - Roberts, Brian W.; Kilgannon, J. Hope; Hunter, Benton R.; Puskarich, Michael A.; Pierce, Lisa; Donnino, Michael; Leary, Marion; Kline, Jeffrey A.; Jones, Alan E.; Shapiro, Nathan I.; Abella, Benjamin S.; Trzeciak, Stephen
Abstract : Background: Studies examining the association between hyperoxia exposure after resuscitation from cardiac arrest and clinical outcomes have reported conflicting results. Our objective was to test the hypothesis that early postresuscitation hyperoxia is associated with poor neurological outcome. Methods: This was a multicenter prospective cohort study. We included adult patients with cardiac arrest who were mechanically ventilated and received targeted temperature management after return of spontaneous circulation. We excluded patients with cardiac arrest caused by trauma or sepsis. Per protocol, partial pressure of arterial oxygen (PaO2 ) was measured at 1 and 6 hours after return of spontaneous circulation. Hyperoxia was defined as a PaO2 >300 mm Hg during the initial 6 hours after return of spontaneous circulation. The primary outcome was poor neurological function at hospital discharge, defined as a modified Rankin Scale score >3. Multivariable generalized linear regression with a log link was used to test the association between PaO2 and poor neurological outcome. To assess whether there was an association between other supranormal PaO2 levels and poor neurological outcome, we used other PaO2 cut points to define hyperoxia (ie, 100, 150, 200, 250, 350, 400 mm Hg). Results: Of the 280 patients included, 105 (38%) had exposure to hyperoxia. Poor neurological function at hospital discharge occurred in 70% of patients in the entire cohort and in 77% versus 65% among patients with versus without exposure to hyperoxia respectively (absolute risk difference, 12%; 95% confidence interval, 1–23). Hyperoxia was independently associated with poor neurological function (relative risk, 1.23; 95% confidence interval, 1.11–1.35). On multivariable analysis, a 1-hour-longer duration of hyperoxia exposure was associated with a 3% increase in risk of poor neurological outcome (relative risk, 1.03; 95% confidence interval, 1.02–1.05). We found that the association with poor neurological outcome began at ≥300 mm Hg. Conclusions: Early hyperoxia exposure after resuscitation from cardiac arrest was independently associated with poor neurological function at hospital discharge. Abstract : Supplemental Digital Content is available in the text.